Evaluation of bacterial load in fresh ejaculates of bovine and buffalo bull semen in Himachal Pradesh - JASIAL, SANDEEP; KATOCH, R C; CHACHARA, DEEPTI; MAHAJAN, ARVIND (The Indian Journal of Animal Sciences, 2013)
Fresh semen (75) ejaculates from breeding bulls (16 cow bulls and 6 buffalo bulls) were studied for bacterial load and the type of bacteria present. The bovine bulls (33.3%) and buffalo bulls (24.1 %) carried the bacterial load from 10 000 to 50000/ml and 100 to 5 000/ml respectively. On an average bacterial count per ml of neat semen ranged from 5 000 to 56 000 in 46 ejaculates of bovine bulls and 4 100 to 18000 in 29 ejaculates of buffalo bulls. The different microorganisms as staphylococci (19), micrococci (1), corynebacteria (2), members of Enterobacteriaceae (12) and anthracoids (49) were isolated from semen.